Takaful practice in Nigeria: history, present and future - Aliyu Ardo, Abubakar; Saiti, Buerhan (European Research Centre for Islamic Finance, 2017)
The development of a robust financial system is an important objective especially for a country like Nigeria, being a formidable force on the African continent. As the country aspires to become a major international financial centre in the continent by the year 2020, the development of Takaful as a major segment of Islamic finance remains paramount. Despite government’s effort and the huge potentials for such a unique service, the growth in Takaful operations is still at a nascent after over a decade of existence. Takaful ought to have recorded great success in Nigeria considering several positive factors, unfortunately, which has not been the case. Using a qualitative library research method, this paper provides an overview of Takaful with emphasis on its practice in Nigeria over the years. The paper also further explores the challenges hindering the development of Takaful in Nigeria especially on the legal aspect. Consequently, certain recommendations have been made to reverse the ugly trend. As a matter of urgency, the issues raised need to be addressed to facilitate accelerated development of Takaful operations and contribute towards achieving the much-needed revitalization of the Nigerian financial system